(18)F-fluorodeoxyglucose positron emission tomography/computed tomography of giant cell arteritis with lower extremity involvement in association with polymyalgia rheumatica - Panda, Ananya (World J Nucl Med, 2020)
An 80-year-old man presented with new-onset pain in the shoulders and lower extremities and elevated serum inflammatory markers. A clinical diagnosis of polymyalgia rheumatica (PMR) was made, but there was a suboptimal response to glucocorticoid therapy, prompting further evaluation. (18)F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) revealed intense FDG uptake in the arteries of the bilateral lower extremities, head, and neck, but sparing the aorta, suggestive of an uncommon pattern of giant cell arteritis (GCA). There were also imaging signs consistent with PMR, including FDG uptake in the synovium of large joints. This case highlights the uncommon manifestation of GCA with lower extremity involvement and sparing of the aorta. The combination of FDG PET imaging features and elevated serum markers obviated the need for invasive biopsy. One might also conclude that standard FDG PET/CT imaging protocols covering orbits/vertex to thighs incompletely evaluate the extent of arterial distribution of GCA.